The Correlation between Knowledge Level and Gout Prevention Behavior among the Elderly in Kresnomulyo Village, Ambarawa District, Pringsewu Regency, Lampung - Winabila, Putri; Safutri, Wina; Pratiwi, Mida; Dwiningrum, Riza (LPPM Universitas Dhyana Pura, 2025)
Gout is a purine metabolism disorder characterized by increased levels of uric acid in the blood, leading to the accumulation of uric acid crystals and joint pain, particularly among the elderly. Knowledge about gout prevention behavior in the elderly significantly affects the success of gout management. Gout management is essential to prevent long-term complications such as joint damage and kidney stones. This study aims to determine the relationship between knowledge level and gout prevention behavior among the elderly in Kresnomulyo Village, Ambarawa District, Pringsewu Regency, Lampung. This study was a descriptive quantitative study with a cross-sectional design. The sampling technique used purposive sampling based on inclusion and exclusion criteria, with a total of 110 respondents. The results showed that 31% of respondents had a moderate level of knowledge, while 79% had a low level of knowledge. In terms of behavior, 100% of respondents exhibited poor gout prevention behavior. The Chi-Square test results showed an Asymp. Sig value of 0.000 < 0.05, indicating a significant relationship between knowledge and gout prevention behavior among the elderly in Kresnomulyo Village, Ambarawa District, Pringsewu Regency, Lampung. Village administrators can actively contribute to enhancing community awareness about gout prevention by conducting educational initiatives and implementing practical programs. Furthermore, promoting sufficient water intake, regular physical activity, and a balanced diet through Posyandu or local community gatherings is essential.